The Ortega's Phenomenology of Love - Tillería Aqueveque, Leopoldo (2020)
The article discusses the phenomenology of love in the philosophy of Ortega, especially from his work of the mature period, Studies on Love (1939). Therefore, the writing is organized around five concepts that Ortega would describe an essential note to his idea of love: infatuation, delivery, choice, courtly love, and perfection. This reception of Ortega's phenomenology of love acquires greater clarity from the consideration of love as a mode of affectivity proposed, in turn, by Martin Heidegger's phenomenology. Ortega's Love, an aesthetic expression of his philosophy of vital reason, shows the Spanish thinker's concern to explain the love event from the synthesis between reason and life, precisely at the core of our circumstance. This species of phenomenology of love would reveal, to the end, the romantic hero as the only way of being that it could counteract the nihilism that the Spanish faced through his philosophy of life.